Inclusion of Children with Disabilities in Early Childhood Education: Parents’ Perceptions in Rural Areas of Mudzi District, Zimbabwe - Mercy Ncube; Nyuma Barbra Musakanyi (INKLUSI, 2025)
This study examined parents’ perceptions in Mudzi District, Zimbabwe, regarding the inclusion of children with disabilities in early childhood education. Inclusive education is a fundamental right ensuring equal learning for all, yet children with disabilities still face discrimination, stigma, and infrastructural barriers. This qualitative research used structured interviews with 12 parents: 4 parents of children with disabilities and 8 parents of children without disabilities selected through snowball sampling. The findings showed many parents were concerned about teachers’ ability to manage inclusive classrooms effectively. They also felt disappointed by the lack of attention to their children’s needs and the limited learning resources. Economic challenges and cultural beliefs linking disability with misfortune further hinder acceptance. The study underscores the need for improved teacher training, awareness campaigns, and coordinated efforts to support inclusive practices. Penelitian ini mengkaji persepsi orang tua di Distrik Mudzi, Zimbabwe, mengenai inklusi anak penyandang disabilitas dalam pendidikan anak usia dini. Pendidikan inklusif diakui secara global sebagai hak mendasar yang memberi kesempatan belajar setara bagi semua anak. Namun, anak penyandang disabilitas sering menghadapi diskriminasi, sikap negatif, dan hambatan infrastruktur yang membatasi akses. Penelitian kualitatif ini menggunakan wawancara terstruktur dengan 12 orang tua: 4 orang tua anak penyandang disabilitas dan 8 orang tua anak tanpa disabilitas yang dipilih melalui snowball sampling. Temuan menunjukkan banyak orang tua khawatir pada kemampuan guru mengelola kelas inklusif secara efektif. Mereka juga kecewa atas kurangnya perhatian terhadap kebutuhan anak dan terbatasnya sumber belajar. Tantangan ekonomi dan keyakinan budaya yang mengaitkan disabilitas dengan kemalangan turut menghambat penerimaan. Penelitian ini menekankan perlunya peningkatan pelatihan guru, kampanye penyadaran, dan upaya terkoordinasi untuk mendukung praktik inklusif.